Educação militar brasileira : os regulamentos de ensino da Escola de Estado-Maior do exército (1905 - 1937) - Marcusso, Marcus Fernandes (2017)
The Army General Staff School was created in 1905, and its main function was provide Brazilian Army officers to a higher military education that qualified them to serve on the General Staff of the Army. The present thesis analyzes the education regulations of the EEM, trying to identify the type of training planned for official students in the period from 1905 to 1937. The five EEM regulations, published between 1905 and 1934, were consulted. (1905, 1913- 14, 1920, 1929 and 1934-35). The first years of operation of the EEM were marked by simple physical structure, the frequency of a few students and the influence of German military thinking. This scenario changed considerably from 1919, when the Brazilian government contracted a French Military Mission (MMF) to carry out a major reform in the Brazilian Army and the EEM was one of the first military institutions to be reorganized by French officers. The period of French presence from 1919 to 1940 was marked by the construction of its own school building, the increase of courses, the creation of boards, the writing of own textbooks, the introduction of new teaching methods and the training of Brazilian officers to act as instructors and lecturers in the EEM. The non-renewal of the contract with the MMF in 1940 marked the end of the presence of French officers in the structure of the Army and the EEM, but not the influence of their military thinking. The outbreak of the 1930 Revolution provoked intense transformations in the Army, in military education, and consequently in the EEM. In the analysis of official documents is essential to consider, in addition to its content, the historical circumstances they are made, those responsible for its making, and finally, their relationship with the concrete reality. At various times it is seen that the provisions of the regulations found great difficulties in implementation, as evidenced by the reports of the Ministers of War, the Army General Staff Chiefs and some memories of former students and former instructors. These documents are listed as the main sources of research, in which were also consulted documents relating to the French Military Mission, newspapers of the time and extensive bibliography. Another important source were the documents relating to education in EEM: schoolwork, teaching manuals, guidelines for applicants, evaluation, among others. The study on the Army General Staff School provides an in-depth understanding of the formation of the official student of the Brazilian Army, and the relations between the military and civilians in the first decades of the twentieth century.